VERBA DASAR DAN VERBA TURUNAN BAHASA MELAYU PAPUA SERTA PADANANNYA DALAM BAHASA INDONESIA - NFN Supardi (Balai Bahasa Sulawesi Selatan, 2013)
Verba Papuan Malay is very different from the other Malay verbs, especially the Malay language in the westernregion of Indonesia. The study shows that the verb BahasaMelayu Papua is not built on free morphemes suchas affixes and in Indonesian and Malay descent in the western region, but only built on the free morpheme.The data in this study were collected by tapping directly and quoted from the three publications in Papua.The approach used in this study is descriptive pendakatan structural. There is also the method used is thedistributional method. From the analysis result is obtained conclusion. BahasaMelayu Papua verb form of 1)base morpheme, 2) verbs inflectionsi: (1) prefixation is not productive, (2) lexical reduplication AbstrakVerba Bahasa Melayu Papua sangat berbeda dengan verba bahasa Melayu lain, terutama bahasa Melayu yangada di kawasan barat Indonesia, termasuk dengan bahasa Indonesia. Hasil kajian menunjukkan bahwa verbaBahasa Melayu Papua tidak dibangun berdasarkan afiks dan morfem bebas seperti dalam bahasa Indonesiadan keturunan bahasa Melayu di kawasan barat, tetapi hanya dibangun berdasarkan morfem bebas. Data dalampenelitian ini dikumpulkan melalui sadap langsung dan dikutip dari tiga terbitan di Papua. Pendekatan yangdigunakan dalam kajian ini adalah pendakatan deskriptif struktural. Ada pun metode yang digunakan adalahmetode distribusional. Dari hasil analisis diperoleh simpulan. Verba bahasa Melayu Papua berupa 1) morfemdasar, 2) morfem jadian. Verba jadian berupa (1) prefiksasi bersifat tidak produktif, dan (2) reduplikasi leksikal